Estrategias metacognitivas y autoestima en estudiantes del tercer nivel de educación inicial facultad de ciencias de la educacion y humanidades-UNAP 2021 - Grandez Hidalgo, Alexandra Sholange (2023)
The study carried out has the title, Metacognitive strategies and self-esteem in students of the third level of initial education Faculty of Education UNAP 2021, the general objective was to explain the relationship between metacognitive strategies with self-esteem in students of the third level of Initial Education, Faculty of Education; the type of non-experimental, descriptive correlational research, with cross-sectional correlational design. The sample with which we worked were 41 students of the third level of Initial education, the technique used was the survey and the Coopersmith Self-esteem inventory as an instrument. It is concluded that Spearman's rho correlation coefficient = 0.882**, p = 0.000 shows a moderate significant direct relationship between metacognitive strategies and self-esteem, in students of the third level of Initial Education of the Faculty of Education. The result indicates that to the extent that metacognitive strategies are developed in the learning process, the self-esteem of the students of the third level of Initial Education improves significantly; that is, the students present moderate psychological health, can interact in the environment in a healthy way and are not very vulnerable to emotional attacks from the environment and act calmly in any situation.